Práticas de gestão da qualidade, inovação e vantagem competitiva : análise das relações em empresas de manufatura certificadas com a ISO 9001 no Brasil - Oliveira, John Lennon Andrade de (2019)
It is common among organizations to search for strategies with which they can improve their respective performance, as well as gain a competitive advantage over their competitors. Among these strategies are the efforts in terms of quality improvement and the development of innovations that, historically, have been credited as aspects capable of giving competitive advantage to the organizations. The pursuit of better quality performance has led to the emergence of various management practices in the effort to create effective ways to achieve this goal, such as total quality management practices, which are also present in ISO 9001 quality system certifications. However, what are the relationships between quality management practices, innovation and competitive advantage in ISO 9001 certified manufacturing firms in Brazil? Arguments argue that the use of quality management practices is detrimental to innovative performance (MANGIOROTTI; RIILO, 2014), as well as those who defend a positive influence, ie that quality management practices are capable of the emergence of innovations (FLYNN, 1994; PERDOMO-ORTIZ; GONZÁLEZ-BENITO; GALENDE, 2006). Thus, the objective of this work was to investigate the relationships between quality management practices, innovation and competitive advantage, by conducting an empirical study in manufacturing companies certified with ISO 9001 in Brazil. For this, the questionnaire and the theoretical model used in the article by Kafetzopoulos, Gotzamani and Gkana (2015), the only study found by the researcher that empirically investigated the relationships between quality management practices, product and process innovations and competitive advantage. The present research can be classified as descriptive, adopting a quantitative approach, with data collection done by survey. Data collection was performed between October 2018 and January 2019, with the analyzes being completed in February 2019. For the quantitative analysis of the data, descriptive and multivariate statistics techniques were used, such as frequency distributions, modeling of structural equations and other statistical tests with the help of Microsoft Excel®, GPower, IBM SPSS® and SmartPLS© software. The results showed that the adopted model has quality to measure the proposed relationships, besides supporting the previously defined hypotheses. The study concludes by indicating that the results contribute towards the majority of the studies on the subject, that is, that quality management practices have positive and significant relations with the two types of innovation investigated, as well as the respective constructs of innovation have positive relations and significant with competitive advantage. In addition, it also highlights some limitations of the present research, such as the composition of the model, the time of data collection, among others, indicating some proposals for future studies, such as the accomplishment of qualitative studies and the increment of other variables and relations relationships in the model tested.